Women in Bangla Language Movement: Unsung Heroes - Khatun, Mst. Rupali (Mother Language, 2025)
The iconic Language Movement holds great significance in the history of Bengal as well as the globe at large. During this milestone event, the Bengali women had united with the men to take part in the movement crossing the boundary of conservative society. Sufia Ahmed (1932 2020), Rawshan Ara Bachchu (1932-2019) and other women tirelessly took part in various meetings, processions and relevant actions. By the beginning of 1952, the Language Movement took a serious turn. On 21 February the students were determined to violate Section 144 imposed by the government. When the male and female students emerged in groups, shouting slogans, the police resorted to baton charge; even the female students were not excluded. Through a long and hard struggle Bangla language got the status of national language. Simultaneously, the success of the Language Movement greatly increased the self-confidence of women. As a result, women bravely participated in various national agitations that took place later. Moreover, the objective of the research is to analyze how the Bengali women broke the long-standing paternalistic conservatism and got involved in the Language Movement inspired by nationalism. Through this movement tried to uncover the cultural awareness as well as the nature of Bengali women’s progress. It should be mentioned that Analytical method has been followed to prepare this research work. Mother Language, 2025; 9(1): 169-188